2022
DOI: 10.1111/1365-2435.14056
|View full text |Cite
|
Sign up to set email alerts
|

Morphological adaptations linked to flight efficiency and aerial lifestyle determine natal dispersal distance in birds

Abstract: Dispersal is a fundamental ecological and evolutionary process, influencing survival, population dynamics and biogeography (Pigot & Tobias, 2015). Within populations, dispersal is a critical factor regulating resource competition (Waser, 1985) and exposure to parasites and predation (Connell, 1971;Janzen, 1970), as well as inbreeding (Greenwood et al., 1978), demography and population genetics (Clobert et al., 2012;Greenwood & Harvey, 1982). At larger spatiotemporal scales, dispersal can shape patterns of geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 73 publications
3
42
0
Order By: Relevance
“…The importance of flight efficiency, as estimated from wing morphology, in determining dispersal distances in birds supports the already prominent use of wing morphology as a proxy for dispersal ability in ecology and evolution (Claramunt et al, 2012;Sheard et al, 2020;Tobias et al, 2020;Weeks et al, 2022). Like in British birds (Claramunt, 2021), we found that more precise estimates of flight efficiency, such as the aspect ratio and the lift-to-drag ratio, resulted in better predictions of natal dispersal distance (see Appendix, Table S8).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The importance of flight efficiency, as estimated from wing morphology, in determining dispersal distances in birds supports the already prominent use of wing morphology as a proxy for dispersal ability in ecology and evolution (Claramunt et al, 2012;Sheard et al, 2020;Tobias et al, 2020;Weeks et al, 2022). Like in British birds (Claramunt, 2021), we found that more precise estimates of flight efficiency, such as the aspect ratio and the lift-to-drag ratio, resulted in better predictions of natal dispersal distance (see Appendix, Table S8).…”
Section: Discussionsupporting
confidence: 82%
“…Our method, adapted from Paradis 1998), produced dispersal estimates that are standardized, comparable, and easily replicated. These data add to the growing body of dispersal distances estimated from banding data (Martin & Fahrig, 2018;Paradis et al, 1998;Weeks et al, 2022) and will facilitate future comparative analysis. Because of the number of years elapsed between banding and recovery, some breeding dispersal events may have been added, producing an overestimation of natal dispersal distances.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These six continuous traits were ( 1 ) “body mass,” mean unsexed body mass (g) or mean of male and female masses, ( 2 ) “bill length,” mean unsexed bill length (mm) or mean of male and female bill length (exposed culmen), ( 3 ) “egg mass,” mean mass (g) of fresh eggs, ( 4 ) “clutch size,” mean number of eggs per clutch, ( 5 ) “incubation duration,” duration of clutch incubation (days), and ( 6 ) “hand-wing index,” measured as the distance [mm] between the tip of the first secondary feather to the tip of the longest primary feather, divided by total wing chord length and multiplied by 100. Bill dimensions reflect the trophic or dietary niche ( 60 ), and hand-wing index provides a metric of flight efficiency and dispersal ability ( 63 , 64 ). In total, 263 of the original 285 species had complete information for all six traits and were included in analysis of abundance-weighted representation within functional trait space (below).…”
Section: Methodsmentioning
confidence: 99%
“…The study of avian functional diversity has recently gained momentum due to the release of the AVONET database, which provides a complete set of data for eight continuous morphological traits for all the world’s extant bird species (Tobias et al, 2022). Dozens of papers have been published using this data source in just a few months (e.g., Weeks et al, 2022), including several focusing on islands (e.g., Matthews et al, 2022; Soares et al, 2022). An often mentioned issue when studying the functional diversity of birds is the so-called “kiwi problem”.…”
Section: Methodsmentioning
confidence: 99%